KEBIJAKAN STANDAR PEMBIAYAAN DALAM DUNIA PENDIDIKAN - Jaelani, Ahmad; Sahudi, Sahudi; Supiana, Supiana; Zaqiah, Qiqi Yuliati (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Policies are always associated with the public. Public Policy is a binding decision for the public at a strategic level or broadly the nature made by public authorities. Then education financing. Education financing can be interpreted simply as the cost that must be available and needed in organizing education in order to achieve its vision, mission, objectives, objectives, and strategic. Education financing required for the procurement of buildings, facilities and infrastructure, tutoring, teacher salaries, employee salaries and so on. Nowadays, the management of education, especially primary and secondary education, is the responsibility of the local government. With the granting of large authority, it is expected that the government can maximize the ability or capacity of existing regions in terms of education financing. This research is intended to determine the policy of education financing budget, the source of education budget and allocation of education financing. With this research, of course, it is expected to provide benefits both academically and practically. The research method used is a qualitative descriptive approach. Data collection both primary and secondary data using literature riview techniques of online observation and documentation. The results of the study also provide some suggestions including the need for a clear financing mechanism, in the form of standard education costs that must be paid to enter the school.